2006
DOI: 10.1021/ac060376g
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein Characterization Combining Intact Protein and Glycan Analysis by Capillary Electrophoresis-Electrospray Ionization-Mass Spectrometry

Abstract: Glycosylated proteins play important roles in a large number of biological processes. Therefore, a complete characterization in terms of glycan structures and glycoform heterogeneity is needed. In this paper, a combined approach based on glycan and intact glycoprotein analysis by capillary zone electrophoresis-electrospray-mass spectrometry (CZE-ESI-MS) is presented. Based on a new capillary coating, a CZE-ESI-MS method for the separation and characterization of intact glycoproteins has been developed and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 31 publications
1
108
0
Order By: Relevance
“…4,8,10,43,44 These modifications were mainly observed in highly sialylated glycans and include acetylation of sialic acids, N-acetylneuraminic (Neu5Ac) / N-glycolylneuraminic acid (Neu5Gc) variation, and elongation of the glycan chains because of the presence of LacNAc repeats. Up to three modifications occurred per glycan.…”
Section: Detection Of Glycan Modifications In Rhuepomentioning
confidence: 99%
“…4,8,10,43,44 These modifications were mainly observed in highly sialylated glycans and include acetylation of sialic acids, N-acetylneuraminic (Neu5Ac) / N-glycolylneuraminic acid (Neu5Gc) variation, and elongation of the glycan chains because of the presence of LacNAc repeats. Up to three modifications occurred per glycan.…”
Section: Detection Of Glycan Modifications In Rhuepomentioning
confidence: 99%
“…After the CE separation of glycosylated and nonglycosylated peptides, the eluting peptides were automatically spotted onto a MALDI target and their sequences analyzed by MS and MS/MS. A second study reported the analysis of intact glycoproteins and underivatized glycans by CE-MS (121). The CE separation of intact proteins was performed in capillaries coated with either Polybrene or UltraTrol.…”
Section: Protein and Peptide Analysismentioning
confidence: 99%
“…After the CZE-UV and CZE-MS analysis of the intact protein glycans from human, AGP were released by enzymatic deglycosylation which was performed with peptide N-glycosidase F, as described elsewhere [23]. The sample containing the glycans, the deglycosylated protein, and the partially deglycosylated protein was analyzed by CZE-MS.…”
Section: Sample Treatmentmentioning
confidence: 99%